New data on biology and captures of Erimacrus isenbeckii (Decapoda: Cheiragonidae) in the Shelikhov Bay (northern Okhotsk Sea) - D. V. Artemenkov; P. Yu. Ivanov; T. B. Morozov; D. O. Sologub (Известия ТИНРО)
New data on biology of hair crab Erimacrus isenbeckii are presented and ecological and geographical variability of this species is discussed. Molting, growth, sex and size structure of the crab are considered on the data collected in the Shelikhov Bay of the Okhotsk Sea in September-October, 2022. The male : female ratio of E. isenbeckii in the trap catches was 14 : 1. Gender differences in their age, weight, and carapace width were not signiﬁcant (p < 0.05). The maximum size of E. isenbeckii in the Shelikhov Bay was 104 mm that is less the size values at the western coast of Kamchatka, southward from Kamchatka, and in the Aniva Bay of Sakhalin Island, and much smaller the crabs from the waters of Hokkaido Island and Alaska Peninsula. Rather high portion of the males on the 3rd intermolting stage was detected (57 %). The age composition of males varied signiﬁcantly in dependence on stage of molting (p < 0.05). A freshly molted female on the 1st intermolting stage with an unoccluded genital opening was caught together with its exuvia. After molting, within the crab trap, it had increased the width of carapace in 6 mm. This new information could be used in monitoring of the E. isenbeckii population in the Shelikhov Bay.